Energy solutions to the bi-harmonic parabolic equations - Saleh Almuthaybiri; Tarek Saanouni (AIMS Mathematics)
This study explores the threshold of global existence and exponential decay versus finite-time blow-up for solutions to an inhomogeneous nonlinear bi-harmonic heat problem. The novelty is to consider the inhomogeneous source term. The method uses some standard stable sets under the flow of the fourth-order parabolic problem, due to Payne-Sattynger.